2022
DOI: 10.3389/fanim.2022.839906
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Ultra- and Circadian Activity Rhythms of Dairy Cows in Automatic Milking Systems Using the Degree of Functional Coupling—A Pilot Study

Abstract: Ultra- and circadian activity rhythms of animals can provide important insights into animal welfare. The consistency of behavioral patterns is characteristic of healthy organisms, while changes in the regularity of behavioral rhythms may indicate health and stress-related challenges. This pilot study aimed to examine whether dairy cows in free-stall barns with an automatic milking system (AMS) and free cow traffic can develop ultra- and circadian activity rhythms. On 4 dairy farms, pedometers recorded the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…4 ). The automatic milking system has become a standard approach in large farms, and it affects the welfare and health of animals by reducing the percentage of infection [ 125 ]. Any online mastitis diagnosis is achieved by assessing the SCCs, EC, or color.…”
Section: Mastitis Diagnosismentioning
confidence: 99%
“…4 ). The automatic milking system has become a standard approach in large farms, and it affects the welfare and health of animals by reducing the percentage of infection [ 125 ]. Any online mastitis diagnosis is achieved by assessing the SCCs, EC, or color.…”
Section: Mastitis Diagnosismentioning
confidence: 99%
“…As noted above, monitoring behavioural complexity and affect dynamics may also contribute to assessment of social and hedonic dimensions of wellbeing. An important issue for application of real-time monitoring to animal management is the need for thresholds as triggers for intervention (Sun et al 2021;Wagner et al 2021;Fuchs et al 2022). Continuous monitoring of individuals creates the possibility of establishing individualised thresholds that align with persistent differences among individuals in physiological, behavioural and affective characteristics associated with personality.…”
Section: Interpreting These Indicators: Relationships Between Functio...mentioning
confidence: 99%
“…While individualised thresholds may be feasible, it would, nonetheless, be highly desirable to have universal thresholds that do not require alignment with persistent individual differences. Studies by Nunes Marsiglio Sarout et al (2018), Wagner et al (2021) and Fuchs et al (2022) showed some promise for developing general (universal) thresholds for describing deviations in circadian functions.…”
Section: Interpreting These Indicators: Relationships Between Functio...mentioning
confidence: 99%
“…There has been very little use of wearable sensors in calf welfare, especially in newborn calves, where the aim is to have high calf vitality, which can be defined as having the “capacity to live and grow with physical and mental energy and strength” [ 8 ]. This is despite the knowledge that for dairy cows, the consistency of behavioural patterns as measured by circadian rhythms is a characteristic of good health and welfare while changes to the regular patterns can be precursors of health issues [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%